Case Study Identification Of Needed Affairs That Will Have An Impact On Marriage Satisfaction On Workers In Medan In 2020 - Wahyuni; Miskah Afriani; Debi Rahilma (Pena Cendekia Insani, 2021)
One of the causes of the widespread phenomenon of infidelity among workers, both married women and men, is marital dissatisfaction. In 2010, 25.8 percent of men had an affair with a coworker by having sexual relations with them. In 2011, the percentage of male infidelity in Jakarta increased by 65 percent. Meanwhile, it increased by 70% again in 2012, and it increased by 75% again in 2013. It was discovered that the need for cheating in women was due to the tendency of women to workaholic (workaholic), whereas in men it was due to a desire for variety in sex. Furthermore, the work stress factor is high enough in the workplace to cause emotions to feel like sharing with the male work team. The goal of this study is to identify the need for infidelity in workers in the city of Medan in 2020 and how it affects marital satisfaction. According to the study's findings, the identified need that was behind the occurrence of infidelity to the VN informant was due to the unfulfilled need of respect, need of recognition, need of acquisition, need of sex, and need of affiliation among the three (three) informants studied. The unfulfilled need for respect, need for nurturance, need for sex, and need for affiliation is the background to the occurrence of infidelity in SR informants. Meanwhile, the foreign informants behind the infidelity are the unsatisfied needs for sex, nurturance, affiliation, and emotional support.